A SEMIOTIC ANALYSIS ON THE PERCEIVED MEANINGS OF COCA COLA “ANTHEM” VIDEO COMMERCIAL - Melita Leo; Esther H Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study observes the perceived meanings produced by young adult (18 to 30 years old) and older (50 to 65 years old) respondents as respondents from different age group can produce different perceived meanings from each other. The writer’s finding is that in perceiving, young adult respondents tend to emphasize on Coca Cola’s emotional roles. On the other hand, the older respondents emphasize on Coca Cola’s physical roles.